Inhibition of Microbes in the Presence of Lactoferrin and Its Derivatives - Marapana, R. A. U. J. (Journal of Food Science and Technology Nepal, 2009)
Lactoferrin plays an important role in the antimicrobial defense through iron binding, lipopolysaccharide binding and immunomodulation and it appears to have a wide variety of uses in biological systems and is considered a first line immune defense in the human body. Though a natural component of cows and human mother's milk, lactoferrin is found through out the human body and occurs in all secretions that bathe mucous membranes such as saliva, tears bronchial and nasal secretions, hepatic bile, pancreatic fluids, and is an essential factor in the immune response. Research using various animal models has found the ingestion of lactoferrin to have direct protective effects on the regulation and modulation of the immune system. Wide spectrums of functions are ascribed to lactoferrin. Lactoferrin has also been found to both directly and indirectly inhibit several viruses that cause diseases in humans. It directly inhibits viruses by binding to receptor sites, thus preventing the virus from infecting healthy cells. In addition, lactoferrin indirectly kills or inhibits viruses by augmenting the systemic immune response to a viral invasion. Many researches studied the antifungal effect of lactoferrin via its iron binding capacity and showed potent inhibitory effect on fungal growth. Key Words: Lactoferrin; Derivatives; Antibacterial; Antiviral; Antifungus Journal of Food Science & Technology Nepal Vol 4, September, 2008 Page: 12-17